2020
DOI: 10.1007/s11356-020-07696-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dissolved organic phase composition and salinity on the engineered sulfate application in a flow-through system

Abstract: Engineered sulfate application has been proposed as an effective remedy to enhance the rate-limited biodegradation of petroleumhydrocarbon-contaminated subsurface environments, but the effects of dissolved organic phase composition and salinity on the efficiency of this method are unknown. A series of flow-through experiments were conducted for 150 days and dissolved benzene, toluene, naphthalene, and 1-methylnaphthalene were injected under sulfate-reducing and three different salinity conditions for 80 pore v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…However, to the best of our knowledge, there is no study that explores the effects of salinity on the engineered sulfate injection as a remediation method in the organic contaminated subsurface systems. Shafieiyoun et al (2020) in a series of flow-through experiments showed that the overall effects of salinity on organic compounds degradation under sulfatereducing conditions are affected by substrate interactions and NAPL composition. The goal of this study was to delineate the net influence of salinity on the remediation of a hydrocarbon plume by a sequential sulfate injection scenario in a (semi)-arid brackish coastal soil environment, and hence, a single organic contaminant was chosen for the purpose of this evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge, there is no study that explores the effects of salinity on the engineered sulfate injection as a remediation method in the organic contaminated subsurface systems. Shafieiyoun et al (2020) in a series of flow-through experiments showed that the overall effects of salinity on organic compounds degradation under sulfatereducing conditions are affected by substrate interactions and NAPL composition. The goal of this study was to delineate the net influence of salinity on the remediation of a hydrocarbon plume by a sequential sulfate injection scenario in a (semi)-arid brackish coastal soil environment, and hence, a single organic contaminant was chosen for the purpose of this evaluation.…”
Section: Introductionmentioning
confidence: 99%